Students' Understanding of The Equal Sign Based on Their Learning Experience in Arithmetic - Lia Ardiansari; Didi Suryadi; Dadan Dasari (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
The equal sign is an important concept in learning mathematics karena it is used in almost all branches of mathematics, but not many studies in Indonesia have made the equal sign the focus of research. This study aims to explore how students from elementary school to college students understand the equal sign in the context of arithmetic and algebra at school. A qualitative comparative analysis can be used to analyze several cases in complex situations so that it fits the purpose of this study. Participants consisted of 6 elementary school students, 14 junior high school students, 7 high school students and 3 college students in Bandung. The results of the study indicate that the equal sign is still interpreted narrowly as "result" or a sign to put the Menjawab, and has dependence on computational methods in solving problems and drawing conclusions. Thus, it can be concluded that students' understanding of the equal sign is still at the basic level. The results of this study show evidence that the operational meaning of the equal sign that students have when learning arithmetic will not change by itself without the stimulus provided by the teacher, and even tends to cause obstacles when students learn equations in algebra.Tanda sama dengan merupakan konsep penting dalam pembelajaran matematika karena digunakan pada hampir seluruh cabang matematika, namun belum banyak penelitian di Indonesia yang menjadikan tanda sama dengan sebagai fokus penelitian. Penelitian ini bertujuan untuk mengeksplorasi bagaimana para siswa dari mulai sekolah dasar hingga mahasiswa memahami tanda sama dengan dalam konteks aritmatika dan aljabar di sekolah. A qualitative comparative analysis dapat digunakan untuk menganalisis beberapa kasus dalam situasi yang kompleks sehingga sesuai dengan tujuan penelitian ini. Partisipan terdiri dari 6 siswa SD, 14 siswa SMP, 7 siswa SMA dan 3 Mahasiswa di Bandung. Hasil penelitian menunjukkan bahwa tanda sama dengan masih dimaknai secara sempit yaitu sebagai “menghasilkan” atau tanda untuk meletakkan jawaban, serta memiliki kebergantungan terhadap metode komputasi dalam menyelesaikan masalah dan mengambil kesimpulan. Dengan demikian, dapat disimpulkan bahwa pemahaman siswa tentang tanda sama dengan masih berada di tingkat dasar.